Case report: The impact of percutaneous atrial septal defect closure in pulmonary hypertension with co-existing cor triatriatum sinister and multiple cardiac comorbidities - Tai, I-Hsin; Shyu, Tsung-Cheng; Hsieh, Kai-Sheng; Chen, Ke-Wei; Tsai, Wan-Jane; Wang, Kuo-Yang (Frontiers in Cardiovascular Medicine, 2022)
Cor triatriatum sinister, the left-sided triatrial heart, is a rare congenital anomaly with diverse theories regarding its genesis. Failure of incorporation of the common pulmonary vein into the LA is the most widely accepted theory of the embryogenesis of cor triatriatum sinister. Accordingly, cor triatriatm sinister may produce pulmonary venous obstruction and result in post-capillary pulmonary hypertension in the setting of restricted fenestration. High proportion of cor triatriatum sinister patients had associated secundum atrial septal defect. Pre-capillary pulmonary hypertension, which is unusual in patients with small atrial septal defect (<2.0cm), is probably not as rare as some reports indicate when combined with complex comorbidities. The conventional strategy of atrial septal defect closure in patients with pulmonary hypertension associated with cor triatriatum sinister and multiple cardiac anomalies was to be repaired operatively if other cardiac surgery proceeds. There is no practitioner clinical experience of percutaneous atrial septal defect closure. We herein presented the case of an elderly female with pulmonary hypertension associated with cor triatriatum sinister, atrial septal defect, and multiple cardiac anomalies. Despite optimal medical therapy, the biventricular failure deteriorated and clinical stabilization could not be achieved. Transcutaneous atrial septal defect closure was performed. Analysis of the subsequent records showed an initial improvement (perhaps due to the elimination of the left to right shunt) from this intervention, but the long-term impact does not appear favorable (suggested due to uncorrected multiple cardiac anomalies). To the best of our knowledge, this is the first clinical experience to show that partial treatment of combined pre-and post-capillary pulmonary hypertension by eliminating the pre-capillary component may not have a significant benefit, and thus, total correction should be considered unless contraindicated.